Blair, Margaret (audio interview #3 of 5) - Blair, Margaret; Hickman, Vera, interviewer
INTERVIEW DESCRIPTION - This is the third of five interviews with Margaret Blair. They were conducted by a friend who she met when she moved to Long Beach; the friend supported many of the same causes and belonged to the same organizations as Blair. The interviewer was also enrolled an oral history class through CSULB's Senior Citizen fee waiver program. The audio quality of this interview is good. 6/22/1984